Effect of moringa foliage supplementation on in vitro ruminal gas production kinetics and substrate degradation in cattle - DUTTA, NARAYAN; WANKHEDE, S D; TAMBE, M B; KAUR, N; SINGH, P; JADHAV, S E; PATTANAIK, A. K. (The Indian Journal of Animal Sciences, 2022)
This study explored the influence of moringa (Moringa oleifera; MO) foliage supplementation on in vitro ruminal gas production kinetics and substrate degradation in cattle. In vitro fermentation study was carried out with two types of substrates, viz. wheat straw (WS) and WS plus concentrate mixture (CM; 60:40) in cattle rumen inoculum. The MO was incorporated to both the substrates at 0, 5, 10, 20, 30, 40 and 50% levels of total dry matter. The substrates were incubated up to 24 h and substrate degradation was measured. The in vitro gas production kinetics was performed with 8 different (0, 5, 10, 20, 30, 40, 50 and 100%) levels of MO with WS substrate and incubated at 0, 3, 6, 9, 12, 24, 36, 48 and 72 h. The MO addition increased the total gas volume (ml/200 mg) up to 50% level, though, it was analogous when WS and CM based substrate was used. The truly degradable organic matter in rumen (TDOMR) was increased with MO supplementation from 10% onwards. The microbial biomass production (MBP) and partitioning factor (PF) were higher on 30% onwards MO levels. Addition of MO increased the gas production at 24 h from 30% onwards, however, cumulative gas production at 72 h was higher in control (CON). The potential gas production (b) was higher for CON than MO substrates. Fractional rate of fermentation (c) increased from 10 to 100% MO levels. The half time (t1/2) of gas production was substantially reduced with MO supplementation. The volume of gas at t1/2 was significantly lower at 30%. TDOMR was analogous amongst the treatments, however, MBP and PF were higher at 30% level relative to 10 and 20% MO levels. Hence, it may be deduced that supplementation of moringa foliage to cereal straw-based substrate considerably improved the gas production, fractional rate of fermentation, TDOMR, MBP and PF in cattle inoculum.